Tandur Berkemas In Learning Mathematics - Winarno Winarno; Hendri Handoko (EduMa: Mathematics education learning and teaching, 2020)
Research objectives for increasing (1) independence; (2) problem solving skills; and (3) students' problem solving abilities in learning mathematics through the TandurBerkemas model of three dimensional material. The results showed an increase in all three aspects of learning outcomes, namely independence, skills, and student learning achievement. Independence increased from 58.82% to 100%, skills 47.06% to 100%, and learning achievement 64.71% to 97.06%.